The competitiveness of Finnish firms in the changing business landscape - Karhu, Anna; Haaja, Eini; Mäkinen, Hanna (Finland, 2026)
This report explores the pressures caused by megatrends and sudden disruptions in the international
business environment, as well as the influences these have on companies. Specifically, this report focuses
on Finnish companies in the Nordic and the EU contexts. In doing so, the report aims to address the
following question: How are megatrends and disruptions interpreted, and how do systems and companies
respond to them? Building on a fresh synthesis of recent academic research, industry reports, statistical
data and qualitative interviews and workshop discussions, the report highlights how (1) megatrends
and geopolitical developments may influence the competitiveness of Finnish firms dramatically, (2)
Finland in general is searching for its identity and new ‘success story’, (3) key actors at different levels
have varying views of the situation, and (4) the future meaning of competitiveness itself deserves careful
reconsideration in the changing business landscape.